Absolute Configuration Determination of Chiral API Molecules by MicroED Analysis of Cocrystal Powders Formed Based on Cocrystal Propensity Prediction Calculations. Issue 14 (6th February 2023) - Shah, Harsh S.; Yuan, Jiuchuang; Xie, Tian; Yang, Zhuocen; Chang, Chao; Greenwell, Chandler; Zeng, Qun; Sun, GuangXu; Read, Brandon N.; Wilson, Timothy S.; Valle, Henry U.; Kuang, Shanming; et al.
Abstract: Establishing the absolute configuration of chiral active pharmaceutical ingredients (APIs) is of great importance. Single crystal X‐ray diffraction (scXRD) has traditionally been the method of choice for such analysis, but scXRD requires the growth of large crystals, which can be challenging. Here, we present a method for determining absolute configuration that does not rely on the growth of large crystals. By examining microcrystals formed with chiral probes (small chiral compounds such as amino acids), absolute configuration can be unambiguously determined by microcrystal electron diffraction (MicroED). Our streamlined method employs three steps: (1) virtual screening to identify promising chiral probes, (2) experimental cocrystal screening and (3) structure determination by MicroED and absolute configuration assignment. We successfully applied this method to analyze two chiral API molecules currently on the market for which scXRD was not used to determine absolute configuration. Abstract : A new and robust pipeline for absolute configuration determination is presented here. First, virtual screening selects chiral probes compatible with the active pharmaceutical ingredient (API). Second, crystallization trials produce microcrystals suitable for analysis without further optimization. Finally, MicroED is used to determine the crystal structure. The absolute configuration of the API can be confidently assigned relative to the chiral probe.